The U.S. Water Data Gap—A Survey of State‐Level Water Data Platforms to Inform the Development of a National Water Portal. Issue 4 (25th April 2019) - Josset, Laureline; Allaire, Maura; Hayek, Carolyn; Rising, James; Thomas, Chacko; Lall, Upmanu
Abstract : Water data play a crucial role in the development and assessment of sustainable water management strategies. Water resource assessments are needed for the planning, management, and the evaluation of current practices. They require environmental, climatic, hydrologic, hydrogeologic, industrial, agricultural, energy, and socioeconomic data to assess and accurately project the supply of and demand for water services. Given this context, we provide a review of the current state of publicly available water data in the United States. While considerable progress has been made in data science and model development in recent years, data limitations continue to hamper analytics. A brief overview of the water data sets available at the federal level is used to highlight the gaps in readily accessible water data in the United States. Then, we present a systematic review of 275 websites that provide water information collected at the state level. Data platforms are evaluated based on content (ground and surface water, water quality, and water use information) along with the analytical and exploratory tools that are offered. Wev discuss the degree to which existing state‐level data sets could enrich the data available from federal sources and review some recent technological developments and initiatives that may modernize water data. We argue that a national water data portal, more comprehensive than the U.S. Energy Information Administration, addressing the significant gaps and centralizing water data is critical. It would serve to quantify the risks emerging from growing water stress and aging infrastructure and to better inform water management and investment decisions. Plain Language Summary: Water data are essential to describe the state of our resources. They enable the assessment of risks, the evaluation of management decisions, and the design of infrastructure. To adequately manage water, it is necessary to have information not only on climate, the environment, the rivers, and the aquifers but also on the dams and canals that store and divert water, the use of water, and the laws that affect the attribution and distribution of water. Current data limitations stand out as the Achilles heel to promote a sustainable and resilient water management. After a brief overview of the shortcomings of the current readily accessible federal water data, we present results from a systematic review of 275 websites hosting water information collected at the state level. We categorize and evaluate the data platforms based on content (ground and surface water, water quality, water use, and water finance) along with the tools that are offered to interpret and make use of the data. We conclude with a discussion on the degree to which the reviewed data sets at the state level could address the gap in federal data sets. We argue that a national water data portal is critical to understand the growing water risks from extensive use, climate, and aging infrastructure and to better inform water management. Key Points: We discuss key data gaps in ground and surface water, quality, use, and financial data that hinder water management in the United States We review state‐level approaches to online platform for water data, analytics, visualization, and projections, identifying content and tools We conclude with recommendations for the development of a national water data portal to inform public and private decisions